TRIZ Trends of Engineering System Evolution of Silver Sinter-ing Tools Used to Produce Power Module in Hybrids and Electric Vehicles - Shyong, Siow Kim; Foo, Chen Tiam; Xin, Yong Zhen (International Journal of Engineering and Technology, 2018)
Silver sintering is used for bonding of semiconductor dies to the substrate as part of a power module/device packaging. Power-module consisting inverters and converters are used to manage the electric drive systems in the hybrids and electric vehicles (HEVs).Â Many pressure-sintering tools and processes have been patented to produce reliable sintered silver joints for these power applications, and those invented by Siemens, Infineon Technologies, Danfoss, and Valtion (VTT) are analyzed based on the Theory of Inventive Problem Solving (TRIZ) framework. The level of inventiveness for each patent is evaluated, and respective function analysis is conducted to understand the interactions of the components in each sintering tool. This paper is expected to be useful to engineers who are interested in understanding the evolutionary patterns of a technical system especially silver sintering tools